Efektivitas Pembelajaran Daring Selama Masa Pandemi Covid-19 Di Sekolah Menengah Pertama Kota Palangka Raya - Gunarjo Suryanto Budi (Jurnal Ilmiah Kanderang Tingang, 2022)
This study aims to determine the effectiveness of online learning in science subjects during the COVID-19 pandemic based on the responses of teachers and students from four Junior High Schools (SMP) in the city of Palangka Raya. This study uses a quantitative approach with a survey method. Data collection techniques in this study used a questionnaire. The questionnaire was filled out online in the form of a Google Form which was distributed to the respondents. Respondents in this study were students from four junior high schools (SMP) in the city of Palangka Raya, amounting to 80 people. This study showed that there were 48.75% of students who stated that they wanted learning to be carried out face-to-face, but 63.75% of students felt happy with online learning, and 42.5% of students stated that they were quite serious in participating in the online learning process. In addition, student learning outcomes with online learning obtained as many as 77.5% of students who scored above 75, so it can be said that online learning is quite effective.